2001
DOI: 10.1097/00004647-200101000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal MCP-1 Expression in Response to Remote Nerve Injury

Abstract: Direct injury of the brain is followed by inflammatory responses regulated by cytokines and chemoattractants secreted from resident glia and invading cells of the peripheral immune system. In contrast, after remote lesion of the central nervous system, exemplified here by peripheral transection or crush of the facial and hypoglossal nerve, the locally observed inflammatory activation is most likely triggered by the damaged cells themselves, that is, the injured neurons. The authors investigated the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(79 citation statements)
references
References 36 publications
4
74
1
Order By: Relevance
“…CCL2 has been shown to be produced by astrocytes (46,47) and microglia (47) in the CNS during the development of EAE. Endothelial cells (48,49) and neurons (50) have also been shown to express CCL2. However, these cell types, like astrocytes and microglia, would be incapable of CCL2 expression in the CNS CCL2-deficient chimeric mouse.…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 has been shown to be produced by astrocytes (46,47) and microglia (47) in the CNS during the development of EAE. Endothelial cells (48,49) and neurons (50) have also been shown to express CCL2. However, these cell types, like astrocytes and microglia, would be incapable of CCL2 expression in the CNS CCL2-deficient chimeric mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Because it has been found that neurons express high levels of fractalkine and the corresponding receptor (CX3CR1) is expressed in microglia, a functional role of chemokines in the signaling from neurons to microglia has been suggested (42). Although microglial activation was unchanged in CX3CR1 knockout mice, other neuronal chemokines might contribute to the signaling (43). We have recently shown that damaged neurons in vivo and in vitro rapidly induce the expression of CCL21, and we therefore suggest that CCL21 signals neuronal damage to microglial cells (6).…”
Section: Discussionmentioning
confidence: 99%
“…Using the ependymal route, described by Martino et al (26), allows vectors to distribute throughout cerebrospinal fluid (CSF) and infect ependymal and leptomeningeal cells, which in turn secrete the product of the transgene into the CSF. This route avoids the traumatic effects of tissue injury associated with intraparenchymal and intracerebroventricular injections, which can include chemokine production and disruption of the blood-brain barrier (27)(28)(29)(30).…”
Section: Ifn-␥-induced Chemokines Synergize With Pertussis Toxin To Pmentioning
confidence: 99%